Towards population genomics in non-model species with large genomes : a case study of the marine zooplankton Calanus finmarchicus - Choquet, Marvin; Smolina, Irina Vladimirovna; Dhanasiri, Anusha Krishanthi Shyama; Blanco-Bercial, Leocadio; Kopp, Martina Elisabeth Luise; Jüterbock, Alexander Oliver; Meenakshi Sundaram, Arvind Yegambaram; Hoarau, Galice Guillaume (Royal Society Open Science, 2019)
publishedVersion